ACCOUNTING AND BUDGET REPORTING IN PUBLIC ORGANIZATIONS: A TOOL FOR FISCAL TRANSPARENCY AND SUSTAINABLE GOVERNANCE - Sindarov Sherzod Egamberdiyevich; Makhamadalieva Makhliyokhon Makhamadmurod qizi (Scholar Express Journals, 2025)
This study explores how public sector accounting and budget reporting can strengthen fiscal transparency and promote more sustainable, trustworthy governance. By analyzing data from 125 countries—drawn from the 2023 Open Budget Survey, IPSAS adoption reports, and the 2024 Corruption Perceptions Index—we examine how clear and accessible financial reporting impacts the quality of governance. Our findings show that countries with strong budget transparency systems tend to perform better on key governance indicators, with correlation values ranging from 0.65 to 0.72. Moreover, the use of digital tools significantly enhances transparency, with countries that embrace digital platforms seeing 35% more citizen engagement. These results suggest that transparency tools aren’t just technical measures—they’re powerful instruments for building institutional trust, curbing corruption, and supporting long-term development.
Keywords: Accountability; Budget Reporting; Fiscal Transparency